TEETH DEFORMATION OF NON-CIRCULAR GEARS - Silvia MALÁKOVÁ (Scientific Journal of Silesian University of Technology. Series Transport, 2021)
In practice, gear units whose transmission number is not constant during one revolution are used. Such gears include the proposed elliptical transmission. Its application can be (missing a word?) and the automotive industry. The gears set consists of a pair of identical elliptical gears. The transmission ratio of the designed elliptical gear is not constant. The basic kinematic characteristics of this transmission are described in this work. The deformation in contact point of non - circular gears is determined by the finite element method in this paper. The results are compared with the deformation of the teeth of the spur gears.